Problems Associated with the Recognition and Confirmation of Low-Dose Endocrine Toxicities - John Ashby (SAGE Publishing, 2003)
Our attempts to confirm reports of low-dose/hormetic effects in rodent endocrine toxicity studies are reviewed. It is concluded that our present failure to confirm any such effects is due, in large part, to a general lack of understanding of confounding influences and the failure of most investigators to confirm their findings before publication. The major potential confounding factor is suggested to be variability of the parameters under study within control groups, a factor that assumes increased importance when attempting to demonstrate weak low-dose effects. This is illustrated by our studies with bisphenol A in the mouse uterotrophic assay and of finasteride in the Hershberger antiandrogenicity assay. In both of these cases our ability to demonstrate a low-dose effect is dependent on whether concurrent or recent control values are used.